A cellular manufacturing process for a full-scale biodiesel microreactor. (October 2015) - Billo, Richard E.; Oliver, C. Ryan; Charoenwat, Rachaneewan; Dennis, Brian H.; Wilson, Paul A.; Priest, John W.; Beardsley, Heather
Highlights: A design for the "numbering-up" of a large number of microchannel laminae into a full-scale device. A process for fabrication and assembly of a microreactor using low-cost commercial fabrication equipment. First work to describe the full scale-up of a biodiesel microreactor beyond bench top scale. Abstract: A cellular manufacturing process was developed for fabrication and assembly of a full-scale biodiesel microreactor capable of producing biodiesel fuel at the rate of 2.47 L/min and at a capacity of over 1.2 million liters of fuel per year. The scale-up of the microreactor was done through fabrication of over 14, 000 individual microchannel laminae, and assembly of these laminae into a hierarchical system of modules and manifolds, thus duplicating many times over the intensification of the reaction rate per reactor volume that occurs in a single microchannel lamina. The work describes the design of the microreactor, the production process to fabricate and assemble the microreactor, the design of the manufacturing cell, and the testing of the microreactor to verify its performance.